Linear mean free path and quadratic temperature dependence of electron-phonon scattering rate in V82Al18-xFex alloys at low temperature - R. N. Jana; S. Sinha; A. K. Meikap (AIP Advances, 2015)
We have reported a comprehensive study on temperature and disorder dependence of inelastic electron dephasing scattering rate in disordered V82Al18-xFex alloys. The dephasing scattering time has been measured by analysis of low field magnetoresistance using the weak localization theory. In absence of magnetic field the variation of low temperature resistivity rise follows the relation Δ ρ